2018
DOI: 10.1101/383315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional dynamics underlying near-threshold perception of facial emotions: a magnetoencephalography investigation

Abstract: Conscious perception of emotional valence of faces has been proposed to involve topdown and bottom-up information processing. Yet, the underlying neuronal mechanisms of these two processes and the implementation of their cooperation is still unclear. We hypothesized that the networks activated during the interaction of top-down and bottomup processes are the key substrates responsible for perception. We assessed the participation of neural networks involved in conscious perception of emotional stimuli near the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…While in this article, bias was regarded as a nuisance parameter that masks subjects' sensory capacities [34], it is important to underline that in other studies, changes in bias are the parameters of interest. For instance, studying the perception of emotional stimuli in psychiatric diseases, such as depression [35], schizophrenia [36] or autism [37,38] or in healthy subjects [16,39,40], the observed higher or lower thresholds might result from a shift in the sensory bias rather than from altered sensitivity. Since the proposed method differentiates sensitivity and bias, deriving estimates for both, the method might have a wide range of applications in psychotherapy, in which would be interesting to modulate these parameters independently.…”
Section: Discussionmentioning
confidence: 99%
“…While in this article, bias was regarded as a nuisance parameter that masks subjects' sensory capacities [34], it is important to underline that in other studies, changes in bias are the parameters of interest. For instance, studying the perception of emotional stimuli in psychiatric diseases, such as depression [35], schizophrenia [36] or autism [37,38] or in healthy subjects [16,39,40], the observed higher or lower thresholds might result from a shift in the sensory bias rather than from altered sensitivity. Since the proposed method differentiates sensitivity and bias, deriving estimates for both, the method might have a wide range of applications in psychotherapy, in which would be interesting to modulate these parameters independently.…”
Section: Discussionmentioning
confidence: 99%
“…While in this article, bias was regarded as a nuisance parameter that masks subjects' sensory capacities (Witte, Kober, Ninaus, Neuper, & Wood, 2013), it is important to underline that in other studies, changes in bias are the parameters of interest. For instance, studying the perception of emotional stimuli in psychiatric diseases, such as depression (Bourne & Vladeanu, 2013), schizophrenia (Gooding & Tallent, 2002 or autism (Ashwin, Wheelwright, & Baron-Cohen, 2005;Taylor, Workman, & Yeomans, 2012) or in healthy subjects (Kajal, 2018;Kajal et al, 2017;Kajal et al, 2018), the observed higher or lower thresholds might result from a shift in the sensory bias rather than from altered sensitivity. Since the proposed method differentiates sensitivity and bias, deriving estimates for both, the method might have a wide range of applications in psychotherapy, in which would be interesting to modulate these parameters independently.…”
Section: Discussionmentioning
confidence: 99%